Early Cretaceous paleomagnetic results from Marie Byrd Land, West Antarctica: Implications for the Weddellia collage of crustal blocks (Dataset) ... - DiVenere, Vic; Kent, Dennis V.; Dalziel, Ian W. D. (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Early Cretaceous paleomagnetic results from Marie Byrd Land, West Antarctica: Implications for the Weddellia collage of crustal blocks ...